Clinical significance and effect of PRR 11 up-regulation on the malignancy of osteosarcoma - Tan, Rui; Zhao, Chunbing; Lu, Yangcheng; Chen, Lei (Polish Journal of Pathology, 2022)
Osteosarcoma ranks first in both morbidity and mortality among primary bone tumors. This study aimed to investigate the effect of up-regulation of PRR11 on the malignancy of osteosarcoma and its clinical significance. The expression, biological function, related pathways of PRR11 in osteosarcoma and its impact on prognosis were explored through the bioinformatics database. After PRR11 was up-regulated, cell proliferation, invasion, migration and apoptosis were detected by the cell counting kit-8 method, Transwell, scratch, and flow cytometry. PRR11 is highly expressed in a variety of malignant tumors, including osteosarcoma tissue and cells, and has a significant impact on prognosis. Univariate Cox regression analysis revealed that PRR11 was an independent prognostic factor for osteosarcoma. The gene set enrichment analysis results showed that the differential genes were mainly enriched in the biological process of the cell cycle; the protein-protein interaction network mainly interacted with the regulatory genes of the cell cycle. PRR11 promotes the invasion, migration, and proliferation of osteosarcoma cells and inhibits their apoptosis. Comprehensive bioinformatics analysis revealed that PRR11 promotes the malignancy of osteosarcoma cells mainly by participating in cell cycle regulation, and has an important impact on osteosarcoma prognosis. PRR11 may provide the basis for prognosis and treatment in patients with osteosarcoma.